(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was conducted at the Char Kalibari which is situated along the bank of Old Brahmaputra River under Sadar Upazila of Mymensingh district during November 2013 to March 2014 to observe the performance of bitter gourd (Momordica charantia) as arable crop with karanja (Pongamia pinnata L.) trees in an agroforestry system. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications having four treatments viz., T0 (open field condition referred as control), T1 (< 50 cm distance from the tree base), T2 (50-100 cm distance from the tree base) and T3 (>100 cm distance from the tree base). The result showed that all the growth parameters and yield of bitter gourd were significantly influenced by the associated tree component at different distances from the karanja tree base. The highest (1.92 tha-1) fresh yield of bitter gourd was obtained in open field condition compare to any other treatments but no significant different was found from the treatment T3 (distance >100 cm from the tree) while the lowest (0.8 tha-1) in < 50 cm distance from the tree base. It was found that on an average 58.33%, 29.17% and 14.58% yield of bitter gourd were decreased in <50 cm, 50-100 cm and >100 cm distances from karanja tree base compare to open field condition. On the other hand, the growth performance of karanja trees i.e. both height and girth increment was better in sole tree condition compare to tree with bitter gourd condition. Therefore, it can be concluded that tree-crop combination i.e. >100 cm distance from the tree base would be possible although there was some yield loss (14.58%) which was less significant compare to alone bitter gourd. Through this combination we can get diversified product. So, we can follow this agroforestry system to improve char based farming system of Bangladesh during the early establishment period of trees. Res. Agric., Livest. Fish.2(1): 63-73, April 2015